Analisis Efektivitas Kinerja Balanced Scorecard pada BPRS Amanah Rabbaniah Kopo - Marselina, Resya Dwi; Nugraha, Angga; Apriliani, Tifani; Ginanzar, Vian; Sulistiawati, Amelinda (JURNAL MANAJEMEN DAN BISNIS, 2025)
This study aims to analyze the effectiveness of the Balanced Scorecard (BSC) performance system at BPRS Amanah Rabbaniah, Kopo Branch Office. The BSC is utilized as a tool to measure organizational performance comprehensively through four perspectives: financial, customer, internal business processes, and learning and growth. This study employed both qualitative and quantitative approaches, with data obtained from interviews, observations, and financial statement analysis. The findings indicate that the implementation of BSC at BPRS Amanah Rabbaniah is moderately effective, though there are areas requiring improvement, particularly asset efficiency and profit stability. This study recommends strengthening digitalization, improving human resource quality, and evaluating sustainable financial strategies.